2019
DOI: 10.3390/ijerph16060985
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-Temporal Evolution of PM2.5 Concentration and its Socioeconomic Influence Factors in Chinese Cities in 2014–2017

Abstract: PM2.5 is a main source of China’s frequent air pollution. Using real-time monitoring of PM2.5 data in 338 Chinese cities during 2014–2017, this study employed multi-temporal and multi-spatial scale statistical analysis to reveal the temporal and spatial characteristics of PM2.5 patterns and a spatial econometric model to quantify the socio-economic driving factors of PM2.5 concentration changes. The results are as follows: (1) The annual average value of PM2.5 concentration decreased year by year and the month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 42 publications
4
27
0
Order By: Relevance
“…Furthermore, there is sufficient time for most pollutants to gradually diffuse. This finding is partly in agreement with previous studies of Wang et al [32], who showed that the daily average value of PM 2.5 concentration peaked at 10:00 and the valley occurred at 16:00. In contrast, the characteristics of O 3 are opposite to those of the AQI, PM 10 , and PM 2.5 .…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, there is sufficient time for most pollutants to gradually diffuse. This finding is partly in agreement with previous studies of Wang et al [32], who showed that the daily average value of PM 2.5 concentration peaked at 10:00 and the valley occurred at 16:00. In contrast, the characteristics of O 3 are opposite to those of the AQI, PM 10 , and PM 2.5 .…”
Section: Resultssupporting
confidence: 93%
“…Compared with the local spatial autocorrelation, the Getis-Ord G i * is more sensitive to the identification of cold and hot spots, and can fully reflect the high or low value distribution relationship between a certain geographic element and other surrounding elements [ 34 ]. The formula is [ 34 , 35 , 36 , 37 ]: where , n is the number of spatial units (in this study, n = 59), and w ij is the spatial weight matrix, where w ij = 1 if spatial units I and j share a common border and w ij = 0 otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…To highlight the environmental pressure caused by urban overcrowding, the green coverage per capita (GC) in builtup areas is used to measure the level of urban greening. (2) Within the spectrum of city sizes there are enormous differences in population size, built-up area, and industrial structure. Accordingly, real GDP per capita (PG) is chosen to measure the level of economic development of a region.…”
Section: Research Design Dependent Variable: Pm 25 Datamentioning
confidence: 99%
“…With the rapid urbanization and economic development, urban greening has become an urban livability standard and important symbol of residents' well-being ( 1 ). How to achieve a win-win situation for environmental protection and urban development has long been controversial for policymakers ( 2 ). Especially for rapidly-developing countries such as China and India, where rapid urbanization and deteriorating air quality is increasingly threatening the well-being of urban residents ( 3 ), also increasingly demanded for urban planning, policy, and management.…”
Section: Introductionmentioning
confidence: 99%